Awareness on Non- communicable diseases among college students - S, Srivatchava.; V. , Vishnu Priya; R. , Gayathri (International Journal of Psychosocial Rehabilitation, 2020)
Non-communicable diseases (NCDs), also known as chronic diseases, tend to be long-lasting and result from a combination of factors in genetics, physiology, environment, and behavior. Cardiovascular disorders (such as heart attacks and strokes), cancers, chronic respiratory conditions (such as chronic obstructive pulmonary disease and asthma), and diabetes are the major forms of NCDs Most are non-infectious, though there are some non-communicable infectious diseases, such as parasite diseases, in which the life cycle of the parasite does not include direct transmission from host to host. The results obtained were analyzed, and it was found that NCD’s have an effect on one’s day-to-day life.